Localized surface plasmon resonance in bimetallic core-shell nanoparticles - Rahman, Syeda Adiba Mirzana; Chowdhury, Ishmam Salim; Siddha, Simanta; Hasan, Md. Mahmudul (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.